Development of three-dimensional patterning strategies for osteochondral tissue engineering - Sawkins, Michael John (2013)
Fully-realised three-dimensional patterning strategies enable the development of heterogeneous constructs which can recreate tissue architecture and cellular microenvironments over a large range of length scales. This in turn allows the development of more effective tissue models and tissue engineering therapies. The work presented in this thesis was designed to address the development of patterning methodologies and compatible biomaterial formulations.